Nomenclature of Caroxylon imbricatum s.lat. (Amaranthaceae / Chenopodiaceae), with a new combination at variety rank - Nejad Falatoury, Atiye; Iamonico, Duilio; Freitag, Helmut (Phytotaxa, 2017)
A nomenclatural study of the names linked to the critical Caroxylon imbricatum is presented. The names Chenopodium baryosmon, Salsola foetida var. gaetula, S. foetida var. glabrescens, S. foetida var. hirtipetala, S. foetida var. scopiformis, and S. imbricata were studied. Salsola foetida Delile ex Sprengel is lectotypified on a specimen preserved at MPU, while for Chenopodium baryosmon we clarified the statement by Botschantzev (lectotype at BM). Isolectotypes of C. baryosmon are deposited at BM, BR, E, G, K, M, and LE. Salsola foetida Delile ex Moquin-Tandon is an illegitimate name and a homotypic synonym of C. barysmon (Art. 52.2 of the ICN). A taxonomic treatment of the C. imbricatum group is proposed, with two species recognised: C. imbricatum s.lat. (incl. var. imbricatum and var. hirtipetalum comb. nov.) and C. gaetulum.